4- to 8-year complication analysis of 2 'partial collum' femoral stems in primary THA. Issue 1 (January 2021) - Buttaro, Martin A; Slullitel, Pablo A; Oñativia, José I; Nally, Francisco; Andreoli, Mauro; Salcedo, Ricardo; Comba, Fernando M; Piccaluga, Francisco
Objectives: Compare the clinical and radiological outcome of CFP stem with the MiniHip design in a prospective series, with special interest in intraoperative periprosthetic fracture (IPPF). Methods: We prospectively followed 101 cases treated with the MiniHip stem (Group 1) and 89 with the CFP stem (Group 2) operated between 2010 and 2014. No significant demographic differences were observed between both groups. Median follow-up was 72 months. Average stem length was 41% shorter in the MiniHip group ( p < 0.001). Radiological parameters were measured and a logistcic regression model was created to evaluate factors associated with IPPF. Results: Mean mHHS improved from 54 to 95 in the MiniHip group ( p < 0.001) and from 64 to 98 in the CFP group ( p < 0.001). No significant differences were observed in terms of loosening, infection or instability. We observed 7 IPPFs (3.68%), 3 in group 1 and 4 in group 2. After adjusting for confounders, CFP was not associated with a greater risk of IPPF (OR 3.23; 95% CI, 0.250–42.034, p = 0.368), however, a more complex fracture pattern was observed with this stem design. Prior acetabular fractures were associated with IPPF (OR 66.85; 95% CI, 1.142–3911, p = 0.043). Compared to Dorr A femurs, type Dorr B appeared protective against IPPF (OR 0.039; 95% CI, 0.001–1.109, p = 0.058). Valgus alignment tended to increase the risk of IPPF (OR 20.59; 95% CI 0.870–487.221, p = 0.061). Conclusions: MiniHip showed similar radiological outcomes to CFP at short- to mid-term follow-up without increasing IPPFs with a shorter stem length. Given that CFP produced a more complex IPPF pattern, surgeons should be cautious with alignment of this particular design, especially in Dorr A femur.